2020
DOI: 10.1021/acsaem.9b01766
|View full text |Cite
|
Sign up to set email alerts
|

Low Interface Resistance in Solid-State Lithium Batteries Using Spinel LiNi0.5Mn1.5O4(111) Epitaxial Thin Films

Abstract: Solid-state Li batteries that use spinel LiNi0.5Mn1.5O4 as a positive electrode are promising energy-storage devices for portable electronics and electric vehicles. For practical applications of such batteries, it is crucial to understand the ionic conductivity across the solid-electrolyte/electrode interfaces. Here, we demonstrate a low interface resistance of 34 Ω cm2 in solid-state Li batteries using LiNi0.5Mn1.5O4(111) epitaxial thin films with atomically ordered surfaces as the positive electrode. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
2
16
1
Order By: Relevance
“…This atomic‐scale structure profile clearly reveals that LNMO with LPO can have a sharp interface compared with LNMO without LPO, thus enabling smooth Li + transport across the interface in the battery operations. Together with electrochemical impedance measurements on LNMO thin films with two orientations, it was found that even though the LPO/LNMO(111) has atomically ordered interfaces, the interface resistance was fivefold larger than that observed in the LPO/LNMO(001) interface, indicating the anisotropy of the interface resistance in LNMO, which can be attributed to either the differences in the Li diffusion process on the surface of LNMO(111) and LNMO(001) or to the atomic arrangement of the PO 4 network in LPO at the interfaces 68 …”
Section: Scattering‐based X‐ray Techniques For In Situ Studies Of Interfacial Structuresmentioning
confidence: 94%
See 3 more Smart Citations
“…This atomic‐scale structure profile clearly reveals that LNMO with LPO can have a sharp interface compared with LNMO without LPO, thus enabling smooth Li + transport across the interface in the battery operations. Together with electrochemical impedance measurements on LNMO thin films with two orientations, it was found that even though the LPO/LNMO(111) has atomically ordered interfaces, the interface resistance was fivefold larger than that observed in the LPO/LNMO(001) interface, indicating the anisotropy of the interface resistance in LNMO, which can be attributed to either the differences in the Li diffusion process on the surface of LNMO(111) and LNMO(001) or to the atomic arrangement of the PO 4 network in LPO at the interfaces 68 …”
Section: Scattering‐based X‐ray Techniques For In Situ Studies Of Interfacial Structuresmentioning
confidence: 94%
“…The electrolyte or electrode materials are grown epitaxially on proper substrates, by pulsed laser deposition (PLD) or molecular beam epitaxy, to maintain a well‐defined, atomically flat, and in most cases single‐oriented thin‐film surfaces. Hitosugi's group was the first to carry out such studies on SSBs 67–69 . In 2018, they fabricated atomically well‐ordered electrolyte–electrode interfaces using Li 3 PO 4 (LPO) and LCO as the electrolyte and electrode, respectively, to investigate the structures and their influence on the interfacial resistance 69 .…”
Section: Scattering‐based X‐ray Techniques For In Situ Studies Of Interfacial Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent experimental study of the spinel LiNi 0.5 Mn 1.5 O 4 , an anisotropic interface resistance has been found for the ( 100) and ( 111) surfaces of the spinel. [363,364] The resistance at the (111) surface has been measured to be about a factor of 4.5 higher than the resistance at the (100) surface. This observation agrees with the HDNNP predictions which yield an on average about a factor of three higher ionic conductivity in [100] direction than in [111] direction.…”
Section: Anisotropic Ionic Conductionmentioning
confidence: 92%